DETERMINAN PENINGKATAN KINERJA PEGAWAI: ANALISIS PENGARUH GAYA KEPEMIMPINAN, PELATIHAN, DAN MOTIVASI EKSTRINSIK - Diyas Timor Purnawan; Yohanes Joni Pambelum; Meirani Harsasi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to analyze the effect of situational leadership style and training on employee performance and the influence of extrinsic motivation as a mediating variable. The sample used in this study was 75 employees of the National Narcotics Agency within the West Nusa Tenggara Province. The data collection technique used is to use a questionnaire that has been tested for validity and reliability, further tested using path analysis. The results of the hypothesis test with the SmartPLS 3.0 application showed several findings, including: Situational leadership style has a positive and significant effect on employee performance, Training has a positive but not significant effect on employee performance, Extrinsic motivation has a positive and significant effect on employee performance, Situational leadership styles have a positive and significant effect on extrinsic motivation. Training has a positive and significant effect on extrinsic motivation. Situational leadership style through extrinsic motivation has a positive and significant effect on employee performance, and Training through extrinsic motivation has a positive and significant effect on employee performance